Analisis kemampuan klasifikasi mahasiswa pendidikan biologi pada pembelajaran biosistematik hewan - Hernawati Hernawati; Yayan Sanjaya; Fransisca Sudargo; Any Aryani; Zamzam Nursani; Dita Puspitasari; Try Kurniawan; Rahadian Deden Juansa (Department of Biology Education, Universitas Pendidikan Indonesia, 2021)
This study aims to analyze the classification ability in animal biosystematics learning as the basis for making numerical taxonomies in biology education students. The method in this research consists of qualitative and quantitative analysis. Descriptive method is used for qualitative analysis and correlation method for quantitative analysis. The mixed methods strategy uses simultaneous triangulation because both qualitative and quantitative data are collected at the same time, then compared to identify convergence of differences or combinations of data. The number of students was 57 people who were divided into 11 groups. Ability classification is determined based on indicators that refer to science process skills. The classification ability indicator is made into six indicators, where each indicator is broken down into four sub indicators. The results of the analysis show that the classification abilities of the six indicators are: (1) recording each observation separately 89.04%, (2) looking for similarities and differences of 66.23%, (3) contrasting the features of 57.89%, (4) comparing of group characteristics 67.32%, (5) determining the basis for grouping 73.46%, and (6) connecting the results of observations 76.32%. The ability of individuals to make classifications in animal biosystematic learning reached 71.72%, while in groups it was 71.98%. Based on the results above, it can be concluded that the classification ability of participants in animal biosystematic learning is good with the medium category, this can support in making numerical taxonomy.